Evaluation of Expected Insurance Returns in Extreme Weather Based on CRITIC and Generalized Extreme Value Distribution Methods - Xu, Le; Hu, Wenxi (Transactions on Economics, Business and Management Research, 2024)
The frequency of extreme weather events has become a powerful catalyst for huge economic losses. Payouts for natural disasters have increased significantly, leading to a rapid rise in premium rates, and the phenomenon poses a serious challenge to the profitability of insurance companies. In order to specifically study the impact of extreme weather on the calculation of the expected profit that an insurance company can make from underwriting a policy for a specific landmass, and thus to assess the applicability of insurance in a certain region, this paper, based on the data of economic losses due to extreme weather events in five continents from the EM-DAT database. Using the CRiteria Importance Through Intercriteria Correlation (CRITIC) method and the Generalized Extreme Value (GEV) distribution method, we build a model for assessing the expected profit from insurance and verify the applicability of the model through sensitivity analysis. Finally, we provide a reference for insurance companies’ underwriting strategies, a probabilistic assessment for property owners to insure their properties, and a reference suggestion for communities to enhance their extreme weather risk tolerance.